2010
DOI: 10.1524/zpch.2010.0046
|View full text |Cite
|
Sign up to set email alerts
|

Salt-in-Polymer Electrolytes for Lithium Ion Batteries Based on Organo-Functionalized Polyphosphazenes and Polysiloxanes

Abstract: An overview is given on polymer electrolytes based on organo-functionalized polyphosphazenes and polysiloxanes. Chemical and electrochemical properties are discussed with respect to the synthesis, the choice of side groups and the goal of obtaining membranes and thin films that combine high ionic conductivity and mechanical stability. Electrochemical stability, concentration polarization and the role of transference numbers are discussed with respect to possible applications in lithium batteries. It is shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 83 publications
(102 reference statements)
0
8
0
Order By: Relevance
“…Several processes were adopted to optimize the lithiation process and determine their effect on the ionic conductivity of the nanoscale polymer films. It is widely reported that the size of the counterion (anion) in the lithium salt used in the lithiation process can influence the ionic conductivity . As shown in Figure , as anion size increases from LiCl to LiClO 4 , it promotes the improved dissociation of the salt into Li + and counterion, thereby resulting in reduced ion pairing and improved solvation of Li + by the O atoms present in the siloxane film.…”
Section: Resultsmentioning
confidence: 99%
“…Several processes were adopted to optimize the lithiation process and determine their effect on the ionic conductivity of the nanoscale polymer films. It is widely reported that the size of the counterion (anion) in the lithium salt used in the lithiation process can influence the ionic conductivity . As shown in Figure , as anion size increases from LiCl to LiClO 4 , it promotes the improved dissociation of the salt into Li + and counterion, thereby resulting in reduced ion pairing and improved solvation of Li + by the O atoms present in the siloxane film.…”
Section: Resultsmentioning
confidence: 99%
“…14,15 Conjugating siloxane segments to PEO is reported to increase ionic conductivity and impart improved mechanical and electrochemical stability. [16][17][18][19][20][21][22][23][24] The -Si-O-Sibonds in the siloxane moieties are more ionic than -C-O-Cbonds leading to a more negative charge on the oxygen atom that can chelate Li + . The exible nature and associated free volume of the siloxane linkages further facilitate ionic transport.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, comb-branched block copolymers [254] and cross-linked polymer networks [248] have been found to offer favorable mechanical and electrical properties. This includes polymer electrolytes based on polyphosphazenes [255258] and polysiloxanes [258261], as investigated especially by the groups of Wiemhöfer (Germany) and West (USA).…”
Section: An Evolving Scheme Of Materials Sciencementioning
confidence: 99%